Предмет: Математика,
автор: andreykindly
помогите пожалуйста срочно
Приложения:
![](https://files.topotvet.com/i/589/5892ed12a80e66268a13570d1d856bc4.jpg)
Ответы
Автор ответа:
0
... = ⅕ × (21/10 х - 23/10 у) - ⅖ × ( 31/10 у + 19/10 х)
= ⅕×(21/10х - 23/10у - 2(31/10у + 19/10х))
=⅕ ( 21/10 х - 23/10 у - 31/5 у - 19/5 х) = ⅕ × (-17/10 х - 17/2 у)
= ⅕ ( - (17/10 х + 17/2 у)) = ⅕ ( -17/10 × (х+5у))
= -⅕ × 17/10 × (х+5у)
= - 17/50 × (х +5у)
= -0,34(х+5у)
При х=10, у=-2
- 0,34 (10+5(-2)) = -0,34 (10-10) = -0,34×0 = 0
Похожие вопросы
Предмет: Английский язык,
автор: Аноним
Предмет: Русский язык,
автор: lyolikkonina
Предмет: Английский язык,
автор: Аноним
Предмет: Английский язык,
автор: sanyaXD12
Предмет: Английский язык,
автор: Miwka11111